2008
DOI: 10.1021/jp711565g
|View full text |Cite
|
Sign up to set email alerts
|

Pericyclic versus Pseudopericyclic Reactions. What the Laplacian of the Charge Density, ∇2ρ(r), Has To Say about It? The Case of Cycloaddition Reactions

Abstract: The pseudopericyclic character of a group of cycloaddition reactions is theoretically investigated with the quantum theory of atoms in molecules of Bader at B3LYP/6-311++G(d,p) and MP2/6-311++G(d,p) levels of theory. The analysis of the topology of the Laplacian of the charge density, inverted Delta2rho(r), along the reaction coordinate sets out a clear cut between pericyclic and pseudopericyclic processes and also allows one to account for intermediate cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…26 If ∇ 2 ρ (r) < 0 then there is a shared interaction associated with the covalent and polar bonds and when ∇ 2 ρ (r) > 0, there is a closed shell interaction associated with ionic, hydrogen bonds and van der Waals complexes. Table 6 presents the BCP properties of every bond in the all reactions 1-6 under study.…”
Section: Bond Critical Property Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…26 If ∇ 2 ρ (r) < 0 then there is a shared interaction associated with the covalent and polar bonds and when ∇ 2 ρ (r) > 0, there is a closed shell interaction associated with ionic, hydrogen bonds and van der Waals complexes. Table 6 presents the BCP properties of every bond in the all reactions 1-6 under study.…”
Section: Bond Critical Property Analysismentioning
confidence: 99%
“…Lopez and de Lera et al 20 showed that pseudopericyclic reactions do not show a maximum in ellipticity of the forming bond along the reaction coordinate. Recently ELF, BCP [21][22][23][24][25][26] analyses have also been used to differentiate pericyclic reactions from pseudopericyclic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the formation of the meta enyne as the major product at short reaction times in dichlorometane observed with highly substituted systems and why the cycloadduct became the major product when the reaction was left for longer could not be completely rationalized. The analysis based on QTAIM along the reaction paths connecting the stationary points has been successfully applied to rationalize the mechanism of chemical reactions, such as the DA reactions of unsaturated organoboron dienophiles, 25 the dimerization of cyclopentadiene, 26 the Cope rearrangement of 1,5hexadiene, 27 pericyclic and pseudopericyclic reactions, [28][29][30][31][32][33][34] among others. This study indicated that in the initial stage of the reaction the σ-overlap between the 2p atomic orbitals is more stabilizing for the C-B secondary interaction than for the C-C counterpart, favoring the [4 + 3] pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study on the nature of Cl · · · N interactions in complexes formed between substituted ammonium [NH n (X 3‐n ) (with n = 0, 1, 2, 3 and X = –CH 3 , –F)] as Lewis bases and F–Cl molecule as Lewis acid showed that these complexes result from the interaction between a local maximum with a minimum (or saddle) in the Laplacian distribution . Finally, also pericyclic and pseudopericyclic reactions were studied using the Laplacian of the electron density …”
Section: Introductionmentioning
confidence: 99%
“…[18] Finally, also pericyclic and pseudopericyclic reactions were studied using the Laplacian of the electron density. [19] Similarly, the Atoms in Molecules (AIM) theory is applied in this work to study carbocationic transition states involved in two different reaction mechanisms proposed in the olefin reactions over Brønsted-acid site of zeolite catalyst. This allows us to increase our understanding of stereoelectronic aspects of these chemical reactions.…”
Section: Introductionmentioning
confidence: 99%